Răspuns :
Răspuns:
Explicație pas cu pas:
c) inmultim cu 3
3+2x + (x-1)/2 = (2x-3)/3, numitor comun 6:
18 + 12x + 3x - 3 = 4x - 6
11x = -15 - 6
11x = -21
x = -21/11 = -1si10/11
e) 1 - [2 - (3-4+x)] = 5
-(2 + 1 - x) = 4
x - 3 = 4
x = 7.
[tex]c)\quad \left\dfrac{3+2\cdot x}{3}+\dfrac{x-1}{6} = \dfrac{2\cdot x-3}{9}\right|\cdot 18\\ \\6(3+2\cdot x)+3(x-1)=2(2\cdot x-3) \\ 18+12\cdot x+3\cdot x-3 = 4\cdot x-6 \\ 15\cdot x+15 = 4\cdot x-6 \\ 11\cdot x = -21 \\ \\ \Rightarrow \boxed{x = -\dfrac{21}{11}}[/tex]